The Role Of Literacy In The Economic Growth Of Cameroon - Dudjo Yen G. Boris; Sonkeng Germain; Njong Mom Aloysius; Tafah Edokat O. Edward (European Scientific Journal, ESJ, 2018)
This paper focuses on how education contributes to economic growth. That is to say that there is a significant relationship between the variables of education and the economic growth of Cameroon. Education is therefore a priority for all nations. This shows the prominent place it occupies in the Constitution of almost every state. There are several studies that have focused on the relationship between education and economic growth of the microeconomic perspective, as macroeconomic, both theoretically and empirically. Empirical studies, which have been carried out everywhere around the world, do not agree with the fact that education has a positive effect on economic growth. The estimation results show that literacy rate, however, remains ambiguous and contradictory when OLS is going to GMM. Investing in Literacy is a challenge for development and it is the heart of poverty reduction process at all levels.